Catholic Anti-Judaism in Reformation Germany: The Case of Johann Eck - Bagchi, David (Studies in church history, 1992)
In any inquiry into Christian attitudes to Judaism in sixteenth-century Germany, exhibit A would undoubtedly be the later writings of Martin Luther against the Jews. The choice for exhibit B presents more of a problem, but a strong case can be made out for an almost contemporary anti-Jewish treatise from the pen of Luther’s staunchest Catholic opponent, Johann Eck. His Refutation of a Jew Pamphlet tends to attract superlatives—‘the most abusive to have been written against the Jews’, ‘the most massive and systematic formulation of the blood libel… the summa of learned discourse on ritual murder’, ‘the absolute nadir of anti-Jewish polemic in the early-modern period’—and something of its unpleasantness can be gauged from the fact that Trachtenberg cited it so often in his disturbing book, The Devil and the Jews. The year in which our Society has chosen to take for its theme ‘Christianity and Judaism’ is also the 450th anniversary of the publication of Eck’s remarkable treatise. It is perhaps an appropriate occasion on which to explore, in rather more detail than has been done before, the context and nature of Eck’s anti-Jewish polemic.